EXPLORING SPEECH ACTS IN THE MAIN CHARACTERS OF AIR 2023 MOVIE: TYPES AND FUNCTIONS - Giyatmi, Giyatmi; Erlangga, Sandi (BASIS (Bahasa dan Sastra Inggris), 2025)
The study aims at describing the types of speech acts in the movie Air (2023) based on Yule's theory of speech acts, and describing their function based on Leech's theory. Using qualitative research methods, the research observes the phenomenon of speech act usage in the movie. The data sources in this study are dialogs from the movie and the script of the movie Air 2023, which were collected through documentation and content analysis. Data analysis is conducted through three stages: data reduction, data presentation, and verification/conclusion, with triangulation of theory and method to ensure validity and reliability. The writers found 50 speech act consisting of direct speech act (22) and indirect speech act (28). The study identifies four main functions of speech acts such as competitive (8), convivial (15), collaborative (22), and conflictive (5). Collaborative function as the most dominant ones relates with the movie's main theme of cooperation and common goals, which makes speech acts a strategic tool in building relationships and achieving mutual success.